In vitro response and Agrobacterium susceptibility of two cultivars of Stylosanthes guianensis - Hoffmann, Lucia Vieira; Vieira, Maria Lucia Carneiro (Pesquisa Agropecuaria Brasileira, 2000)
Two Stylosanthes guianensis (Leguminosae) cultivars, Bandeirantes and Mineirão, were evaluated for their ability to form adventitious shoots in vitro and Agrobacterium susceptibility. To obtain regeneration, several explant sources were used and MS basal medium was supplemented with different concentrations of NAA and BAP. Shoot regeneration occurred in both cultivars from cotyledon and hypocotyl-derived tissues. Stylosanthes was susceptible to wild Agrobacterium strains, since tumor formation was induced. Transient expression of the uidA gene was observed on infected Stylosanthes tissues. Experiments on the effect of the antibiotic cefotaxime and tetracycline, used in transformation assays to Agrobacterium elimination, showed that cefotaxime (250 µg mL-1) has a tendency to reduce shoot regeneration in cv. Bandeirantes explants.